Volumetric Study of the Binary Mixtures Containing a Branched Hexane and an Isomeric Chlorobutane - Guerrero, Hernando; Royo, Félix M.; Lafuente, Carlos (Journal of Applied Solution Chemistry and Modeling, 2015)
This paper reports densities at atmospheric pressure and at three temperatures T = (283.15, 298.15, and 313.15) K of eight binary mixtures involving a branched hexane (3-methylpentane or 2,2-dimethylbutane) and each one of the isomeric chlorobutanes (1-chlorobutane, 2-chlorobutane, 1-chloro-2-methylpropane or 2-chloro-2-methylpropane). Excess volumes were calculated from experimental densities and correlated with the Redlich-Kister equation. Moreover, the excess volumes were analysed using the Prigogine-Flory-Patterson theory.